THE INFLUENCE OF SERVANT LEADERSHIP AND - Rina Afrida; Faisal Matriadi; Adnan (PT. Kreatif Indonesia Satu, 2024)
This study examines the Effect of Servant Leadership and High Performance Work System (HPWS) on Employee Retention and Employee Satisfaction with Employee Engagement as a Mediating Variable. The sample in this study were 138 employees of private hospitals in Medan Municipality. Data collected through questionnaires were analyzed using data analysis methods using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The results of the study show that Servant Leadership and High Performance Work Systems have a significant effect on Employee Engagement, Employee Retention and Employee Performance. And Employee Engagement has a direct effect on Employee Retention and also on Employee Performance. Then in testing the indirect effect of Employee Engagement it was found to play a role as a partial mediating variable in the relationship between the influence of Servant Leadership and High Performance Work System (HPWS) on Employee Retention and Employee Performance.